2014
DOI: 10.1002/jmv.23885
|View full text |Cite
|
Sign up to set email alerts
|

Detection and genotyping of enteroviruses in cerebrospinal fluid in patients in Victoria, Australia, 2007-2013

Abstract: Genotyping by VP1 fragment polymerase chain reaction (PCR) and nucleic acid sequencing to detect enterovirus (EV) genotypes was performed directly on 729 EV PCR positive cerebrospinal fluid (CSF) samples collected between 2007 and 2012 from Victorian hospital inpatients. The overall genotype identification rate from CSF-positive material was 43%. The four most common genotypes identified were Echovirus 6 (24%), Echovirus 30 (17%), Echovirus 25 (10%), and Coxsackievirus A9 (10%), together comprising 61% of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 26 publications
2
17
0
1
Order By: Relevance
“…We confirmed cases to be HPeV-related following review by a cross-disciplinary expert panel (pediatric infectious diseases, microbiology, neurology, and epidemiology) who also categorized cases as confirmed encephalitis or "not encephalitis" by using the International Encephalitis Consortium definition and Brighton criteria. 31,32 Parechovirus molecular testing was performed by using in-house assays: NSW and Victorian cases at the Victorian Infectious Diseases Reference Laboratory, as previously described 34,35 ; Queensland cases at Royal Children's Hospital, Brisbane, according to the protocol described by Benschop et al 36 Suspected encephalitis was defined as encephalopathy (altered level of consciousness, lethargy, or behavior and/or personality change) lasting ≥24 hours with ≥1 of the following: fever, seizures, focal neurologic findings, at least 1 abnormality of CSF (age determined pleocytosis, or elevated protein ≥40 mg/dL), or EEG/neuroimaging findings consistent with encephalitis.…”
Section: Methodsmentioning
confidence: 99%
“…We confirmed cases to be HPeV-related following review by a cross-disciplinary expert panel (pediatric infectious diseases, microbiology, neurology, and epidemiology) who also categorized cases as confirmed encephalitis or "not encephalitis" by using the International Encephalitis Consortium definition and Brighton criteria. 31,32 Parechovirus molecular testing was performed by using in-house assays: NSW and Victorian cases at the Victorian Infectious Diseases Reference Laboratory, as previously described 34,35 ; Queensland cases at Royal Children's Hospital, Brisbane, according to the protocol described by Benschop et al 36 Suspected encephalitis was defined as encephalopathy (altered level of consciousness, lethargy, or behavior and/or personality change) lasting ≥24 hours with ≥1 of the following: fever, seizures, focal neurologic findings, at least 1 abnormality of CSF (age determined pleocytosis, or elevated protein ≥40 mg/dL), or EEG/neuroimaging findings consistent with encephalitis.…”
Section: Methodsmentioning
confidence: 99%
“…RNA was reverse transcribed with random primers using the SensiFAST cDNA Synthesis Kit (Bioline, UK) as per instructions. PCR was performed as previously described for enteroviruses83 and for HPeV using a real-time PCR targeting the 5′-UTR with an established in-house protocol. Briefly this in-house HPeV PCR method uses the primers and probe Parecho-F GTTGTAHGGCCCRYGAAGG, Parecho-Ra GTAKYTGGCCCCARATCAGATC, Parecho-Rb GTATCCAGCCCCARATCAGATC and Parecho-MGBProbe FAM-TGCCCAGAAGGTAC-MGBNFQ with 3 μl of cDNA in a final 20 μl fast master mix (Perfecta qPCR fastmix, Quanta Biosciences, MD, USA) containing primers at 0.9 μM and probe at 0.2 μM.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of previous studies have shown that HEVs are responsible for high percentages of all aseptic meningitis cases, ranging from 43 to 83% (Gharbi et al, 2006;Kumar et al, 2013;Papadakis et al, 2013 This copy is for personal use only -distribution prohibited.…”
mentioning
confidence: 99%